Effects of Ethnic Diversity on Innovation in an Organization - Tahira Khanum, Jalal Din (2011)
This study explores and describes the effects of diversity initiatives to an organization, particularly focusing on ethnicity diversity. Data from 120 participants were collected, the findings were discussed and analyzed. This study will help to understand the needs of the organization and how diversity initiatives can affect the performance of an organization.